Edible Nanocoating: The effect of different types of nanoparticles incorporated with polysaccharide-based materials on antibacterial and antifungal activity / Nur Izzah Azhar, Noor Asnida Asli and Nadya Hajar - Azhar, Nur Izzah; Asli, Noor Asnida; Hajar, Nadya (2021)
The demand rate for fruits supply increases over the years due to their nourish nutrients and rich flavours. However, they can be easily deteriorated by bacterial and fungal activities when stored at room temperature. Regarding this matter, it is necessary to rejuvenate the quality of the fruits by reducing the possibilities of the infection from happening. Polysaccharide-based material is considered as an edible source that promises protection from microbes' contamination if coated on the fruits. Several recognisable metal nanoparticles such as zinc oxide, silver and titanium dioxide nanoparticles could alter the interaction of microorganism development when incorporated with polysaccharides-based materials. The purpose of this review is to study the effect of different types of nanoparticles incorporated with polysaccharide-based materials, for example, chitosan, cellulose, guar gum, xanthan gum and sodium alginate on antibacterial and antifungal activity. The combination of these elements helps to inhibit the growth of microbial colonies and fungus such as Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Phyllosticta psidicola, Colletotrichum gloeosporioides, Alternaria alternata, mould, and yeast. The observation methods of the microorganism were done based on disk-diffusion agar, pour plate agar, nutrient agar, potato dextrose agar, plate count agar and physical counts according to lesion rot on the fruit's surface. Hence, the bacterial and fungal activities can be inhibited when the nanoparticles are incorporated with polysaccharide-based materials and result in increasing the shelf life of the fruits.